Urgensi Parental Involvement dalam Pendidikan Anak Usia Dini di PAUD Inklusi Anak Negeri Yogyakarta - Ulfa, Maria; Ichsan, Ichsan (ACIECE, 2019)
Parents are the first foundation in shaping the character and personality of children. This study aims to provide an overview of the involvement of parents in children's education. as a supporting and determining factor in the development of inclusive education in the family (home) environment. Because of the importance of parental involvement in inclusive education, researchers focus this research on two aspects, namely; how the involvement of parents in early childhood education, and how early childhood education in kindergarten inclusion. The method used to find a phenomenon using a qualitative approach is a escriptive method, understanding children through the stages of psychological development. This research was conducted at Pelangi Kindergarten, a state child of Jogjakarta. Inclusive schools will not develop if communication, cooperation and mutual trust are not established in stimulating aspects of early childhood development